Modelo de negocio para el posicionamiento de la marca hacienda rosa amada en progreso, provincia del Guayas, 2024. - Polastri Salcedo, Xavier Augusto (2025)
The purpose of this project is to propose a business plan to improve the market positioning of Hacienda Rosa Amada located in Progreso, province of Guayas. The existing need within this business lies in the lack of strategic planning to take advantage of the tourist resources it has, therefore, a strategic design capable of directing its implementation is encouraged in the study. The research methodology was a mixed approach and exploratory and descriptive type. The base population was determined from the province of Guayas where 2,115,584 inhabitants (men and women) range between 20 and 64 years old and 59.9% are in a range of 20 to 39 years old, which creates an infinite population. The instrument applied was the survey due to its ability to obtain weighting of the degree of preference and profiles of the target audience. The main results of the market study showed that it is a competitive sector, concluding that positioning through Corporate Identity strategies with SEO, SEM and SMM dissemination methods is ideal.